What does the law have to do with our motives? Notes on the claims of Razian authorities - Faggion, Andrea (Pensando - Revista de Filosofia, 2025)
Joseph Raz’s Pre-emption Thesis asserts that directives from authorities create reasons for actions that should replace other favorable reasons, not just be added to them. This means that, from a legal authority’s perspective, according to Raz, legal norms should motivate subjects to act. However, this thesis seems to conflict with Raz’s own view that the law requires only external conformity to its norms. This objection is recurring. I will respond to that criticism by arguing that, despite the law not sanctioning violations of the moral obligation of pre-emption, the claim that such an obligation exists still needs to accompany any other obligation the law imposes, due to its claim to legitimacy.